PENGEMBANGAN BUKU AJAR ALJABAR LINIER BERBASIS MATLAB MOBILE UNTUK MENUNJANG PEMBELAJARAN DARING - Restu Lusiana; Reza Kusuma Setyansah (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Learning mathematics online, especially in Linear Algebra courses requires mathematical software-based teaching materials, to strengthen the understanding of numerical concepts. The purpose of this research is to produce MATLAB Mobile-based textbooks that are suitable to support online learning. This development research uses a 4-D model containing 4 stages, namely Define, Design, Develop, and Disseminate. This research was conducted at the Mathematics Education Study Program, the University of PGRI Madiun with 20 students as the subject of the fourth semester. The research instrument and data collection in this study used validation sheets, response questionnaires, and learning outcomes tests. Data analysis of the validation sheet and questionnaire used the Likert scale and the Guttman scale, while the data analysis of the learning outcomes test used the Normalized Gain Score (n-Gain). This study produced a Linear Algebra textbook based on MATLAB Mobile to support online learning during the Covid 19 pandemic with a validity percentage of 86,5% (valid), practicality percentage 83,4% (practical), and an n-Gain score of 46,7 (moderately effectiveness). So that the textbooks developed are suitable to support online learning.